Numerical studies of the influence of various geometrical features of a multispiked connecting scaffold prototype on mechanical stresses in peri-implant bone. Issue 9 (4th July 2018) - Uklejewski, Ryszard; Winiecki, Mariusz; Patalas, Adam; Rogala, Piotr
Abstract: The multispiked connecting scaffold (MSC-scaffold) prototype is an essential innovation in the fixation of components of resurfacing arthroplasty (RA) endoprostheses, providing their entirely non-cemented and bone-tissue-preserving fixation in peri-articular bone. An FE study is proposed to evaluate the influence of geometrical features of the MSC-scaffold on the transfer of mechanical load in peri-implant bone. For this study, an FE model of Ti-Alloy MSC-scaffold prototype embedded in a bilinear elastic, transversely isotropic bone material was built. For the compressive load on the MSC-scaffold, maps of Huber-Mises-Hencky (HMH) stress in peri-implant bone were determined. The influence of the distance between the bases of neighbouring spikes, the apex angle of spikes, and the height of the spherical cup of spikes of the MSC-scaffold were analysed. It was found that the changes in the distance between the bases of neighbouring spikes from 0.2 to 0.5 mm cause the HMH stress to increase in bone material by 32%. The changes of the apex angle of spikes from 2° to 4° decrease the HMH stress in bone material by 39%. The changes of height of the spherical cup of spikes from 0 to 0.12 mm increase the HMH stress in bone material by 24%. In conclusion, the spikes' apex angle and the distance between the bases of spikes of the MSC-scaffold are the key geometrical features determining the appropriate MSC-scaffold prototype design. The built FE model was found to be useful in bioengineering design of the novel fixation system for RA endoprostheses by means of the MSC-scaffold.